2010
DOI: 10.1183/09031936.00115409
|View full text |Cite
|
Sign up to set email alerts
|

The respiratory health effects of nitrogen dioxide in children with asthma

Abstract: There is growing evidence that asthma symptoms can be aggravated or events triggered by exposure to indoor nitrogen dioxide (NO 2 ) emitted from unflued gas heating.The impact of NO 2 on the respiratory health of children with asthma was explored as a secondary analysis of a randomised community trial, involving 409 households during the winter period in 2006 (June to September).Geometric mean indoor NO 2 levels were 11.4 mg?m -3, while outdoor NO 2 levels were 7.4 mg?m -3 . Higher indoor NO 2 levels (per logg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 37 publications
2
42
0
1
Order By: Relevance
“…4) to identify, separately for spring and winter, NO 2 levels representing a possible risk for respiratory symptoms. Our results support an association between indoor NO 2 concentration and respiratory health in adolescents: conversely, as previously reported (Gillespie-Bennett et al, 2011), no significant association with outdoor NO 2 concentration was found. In bivariate models, we found that 82% of children reporting chronic phlegm and 78% of those with wheeze in the past 12 months were exposed to higher indoor NO 2 levels.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…4) to identify, separately for spring and winter, NO 2 levels representing a possible risk for respiratory symptoms. Our results support an association between indoor NO 2 concentration and respiratory health in adolescents: conversely, as previously reported (Gillespie-Bennett et al, 2011), no significant association with outdoor NO 2 concentration was found. In bivariate models, we found that 82% of children reporting chronic phlegm and 78% of those with wheeze in the past 12 months were exposed to higher indoor NO 2 levels.…”
Section: Discussionsupporting
confidence: 73%
“…Finally, in children presenting both a personal history of wheeze ever and an exposure to higher indoor NO 2 concentration we found a significantly lower FEF 25-75% with respect to those exposed to lower indoor NO 2 levels. This result is in agreement with a previous paper by Gillespie-Bennett et al (2011) showing the effect of indoor NO 2 exposure on asthmatic children in New Zealand. In this paper, NO 2 exposure was associated with increased frequency of respiratory tract symptoms and decreased FEV 1 .…”
Section: Tablesupporting
confidence: 83%
See 2 more Smart Citations
“…Epidemiological studies have reported relationships between increased ambient of indoor air pollutants including particulate matter (Turner et al, 2011;Faustini et al, 2011;Mehta et al, 2013) and NO 2 (Gillespie-Bennett et al, 2011;Meng et al, 2012) with the increase risks of respiratory tract symptoms. Other studies also correspond with the current study reported that school children in urban density communities had a significant higher prevalence of respiratory symptoms compared to those living in the rural community of low traffic exposures (Skrzypek et al, 2013;Middleton et al, 2010;Siddique et al, 2011;McCormack et al, 2009).…”
Section: Prevalence Of Respiratory Symptomsmentioning
confidence: 99%